Analysis of Variation in Fiber Volume Fraction on Torsional Strength of Epoxy and Polyester Matrix Coconut Fiber Composites - Pangestu, Rendy (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Natural fibers can be employed to enhance the strength and rigidity of composite structures. These fibers can be combined with matrix materials to create composite materials. One specific example of a natural fiber is coconut fiber. Unfortunately, coconut fiber is currently underutilized, leading to organic waste. However, coconut fiber offers several advantages as a substitute for automotive product composites despite facing specific technical challenges. Hence, it is important to understand the potential of coconut fiber composites with epoxy and polyester matrices. This study aimed to assess the capabilities of coconut fiber composites with epoxy and polyester matrices through a torsion test. The study involved conducting torsion tests on composites with varying volume fractions, precisely 25:75, 30:70, 35:65, and 40:60 (coconut fiber fraction to polyester/epoxy fraction). The research entailed creating torsion test specimens and performing the torsion tests. Subsequently, an analysis of the torsion test results was conducted. This research indicates that coconut fiber with an epoxy matrix demonstrated a maximum stress value of 31.27 MPa and a maximum shear strain value of 1.022 rad at a 30% volume fraction. Similarly, coconut fiber composite with a polyester matrix exhibited a maximum stress value of 27.83 MPa and a maximum shear strain value of 0.91 at a 30% volume fraction. Based on these outcomes, it can be concluded that the optimal volume fraction of coconut fiber for producing satisfactory specimens is 30%, regardless of whether the composites have epoxy or polyester matrices.